Thermoelectric Half-Heusler compounds TaFeSb and Ta1-xTixFeSb (0 ≤ x ≤ 0.11): Formation and physical properties. (August 2019) - Grytsiv, A.; Romaka, V.V.; Watson, N.; Rogl, G.; Michor, H.; Hinterleitner, B.; Puchegger, S.; Bauer, E.; Rogl, P.
Abstract: We report on the formation, physical-chemical, as well as elastic and mechanical properties of the novel Half-Heusler (HH) compound TaFeSb that forms during a solid-state reaction from TaSb2 and TaFe2 in the temperature range between 800 and 850 °C. TaFeSb behaves as a semiconductor, and changes the conductivity type either on temperature or composition. Transport properties of TaFeSb and Ta1-x Tix FeSb (0 ≤ x ≤ 0.11) were measured in the temperature range from 4.2 to 823 K, and the effect of titanium on thermoelectric and mechanical properties of Ta1-x Tix FeSb was investigated. The Ta/Ti substitution results in a significant increase of the thermoelectric power factor to exciting values of above 6 mW/m⋅K 2 . In combination with a suppressed phonon thermal conductivity, due to a unique role of Ti, an enhanced figure of merit, ZT900K =1.0 (for Ta0.94 Ti0.06 FeSb) is obtained, close to the highest values reported for Hf-free p-type HH-systems. In addition, experimental results obtained in this study are discussed and analyzed in the context of ab-initio Density Functional Theory (DFT) calculations. Highlights: Physical, chemical and mechanical properties of TaFeSb and Ta1-xTixFeSb are reported. Maximal thermoelectric performance was observed at x = 0.06 Semiconductor TaFeSb changes the conductivity type on temperature or/and composition. Ta/Ti substitution results in a significant decrease of lattice thermal conductivity. Experimental observations agreeing well with DFT calculations.